Exotic nuclear spin behavior in dendritic macromolecules. Issue 46 (18th November 2021) - Saul, Philip; Yang, Shengjun; Mamone, Salvatore; Opazo, Felipe; Meyer, Andreas; Rizzoli, Silvio O.; Glöggler, Stefan
Abstract : Dendrimers display an exotic spin state behavior that we propose to tune for ion sensing. Abstract : Dendrimers are a class of branched, highly symmetric macromolecules that have been shown to be useful for a vast number of different applications. Potential uses as fluorescence sensors, in catalysis and perhaps most importantly in medical applications as drug delivery systems or cytotoxica have been proposed. Herein we report on an exotic behaviour of the nuclear spins in a dendritic macromolecule in the presence of different paramagnetic ions. We show that the stability of the long lived nuclear singlet state, is affected by the presence of Cu(ii ), whereas other ions did not have any influence at all. This effect could not be observed in the case of a simple tripeptide, in which the nuclear singlet stability was influenced by all investigated paramagnetic ions, a potentially useful effect in the development of Cu(ii ) selective probes. By adding a fluorescent marker to our molecule we could show that the nuclear singlet multimer (NUSIMER) is taken up by living cells. Furthermore we were able to show that nuclear singlet state NMR can be used to investigate the NUSIMER in the presence of living cells, showing that an application in in vivo NMR can be feasible.